Physical vapor deposition of amorphous MoS2 nanosheet arrays on carbon cloth for highly reproducible large-area electrocatalysts for the hydrogen evolution reaction1. Issue 38 (14th October 2015) - Zhang, Xing; Zhang, Yun; Yu, Bin-Bin; Yin, Xing-Liang; Jiang, Wen-Jie; Jiang, Yan; Hu, Jin-Song; Wan, Li-Jun
<x xml:space="preserve">Abstract</x> Amorphous MoS2 nanosheet arrays on carbon cloth were directly prepared via a highly reproducible PVD, which exhibited superior catalytic activity and durability for the HER.